Midbrain catecholaminergic neurons co-express α-synuclein and tau in progressive supranuclear palsy - Erro Aguirre, María Elena; Zelaya, María Victoria; Sánchez Ruiz de Gordoa, Javier; Tuñón, María Teresa; Lanciego, José Luis (Frontiers in Neuroanatomy, 2015)
Objective: To analyze the frequency and distribution of α-synuclein deposits in progressive supranuclear palsy (PSP). Methods: The brains of 25 cases of pathologically confirmed PSP were evaluated with immunohistochemistry for α-synuclein and tau. Multiple immunofluorescent stains were applied to analyze the expression of tau and α-synuclein aggregates in catecholaminergic neurons. Patients’ clinical symptoms were retrospectively recorded. Results: Deposits α-synuclein in the form of typical Lewy bodies (LBs) were only found in two PSP cases (8%) that fulfilled the clinical subtype of PSP known as Richardson’s syndrome (RS). LBs were present in the locus ceruleus, substantia nigra pars compacta, basal forebrain, amygdala and cingulated cortex in a distribution mimicking that of Parkinson’s disease. Triple-immunolabeling revealed co-expression of α-synuclein and tau proteins in some tyrosine hydroxilase-positive neurons of the locus ceruleus and substantia nigra pars compacta. Conclusions: There is no apparent clinical correlation between the presence of LBs in PSP. Tau protein co-aggregate with α-synuclein in catecholaminergic neurons of PSP brains suggesting a synergistic interaction between the two proteins. This is in keeping with the current view of neurodegenerative disorders as ‘misfolded protein diseases’.